2002
DOI: 10.1016/s0014-5793(02)03006-5
|View full text |Cite
|
Sign up to set email alerts
|

Cmk2, a novel serine/threonine kinase in fission yeast

Abstract: The cmk2 gene of Schizosaccharomyces pombe encodes a 504 amino acid protein kinase with sequence homology with the calmodulin-dependent protein kinase family. The cmk2 + gene is not essential for cell viability but overexpression of cmk2 + blocks the cell cycle at G2 phase and this inhibition is cdc2-dependent. The Cmk2 is a cytoplasmic protein expressed in a cell cycle-dependent manner, peaking at the G1/S boundary. Overexpression of Cmk2 suppresses ¢ssion yeast DNA replication checkpoint defects but not DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…These proteins have been linked to the post-transcriptional control of gene expression in mammals and yeast (Dahlkvist et al, 1994;Neininger et al, 2002). Fission yeast encodes two MAPKAPKs (Srk1/Mkp1 and Cmk2/Mkp2), which are calmodulin-dependent, dual specificity protein kinases (Alemany et al, 2002). Upon oxidative stress both MAPKAPKs are activated by phosphorylation in a Sty1-dependent manner (Figure 4), with the Srk1-Sty1 interaction being stronger than that of Cmk2-Sty1 (Asp & Sunnerhagen, 2003).…”
Section: The Sty1 Regulatory Signals On Translationmentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins have been linked to the post-transcriptional control of gene expression in mammals and yeast (Dahlkvist et al, 1994;Neininger et al, 2002). Fission yeast encodes two MAPKAPKs (Srk1/Mkp1 and Cmk2/Mkp2), which are calmodulin-dependent, dual specificity protein kinases (Alemany et al, 2002). Upon oxidative stress both MAPKAPKs are activated by phosphorylation in a Sty1-dependent manner (Figure 4), with the Srk1-Sty1 interaction being stronger than that of Cmk2-Sty1 (Asp & Sunnerhagen, 2003).…”
Section: The Sty1 Regulatory Signals On Translationmentioning
confidence: 99%
“…Moreover, it has been shown that the overexpression of a constitutively active form of the Cmk2 MAPKAPK results in low Cdc2 activity and eventually in G2 arrest (Alemany et al, 2002;Rasmussen & Rasmussen, 1994). In response to oxidative stress, Sty1 binds and phosphorylates Cmk2 at the single phosphorylation site (Thr-411) of the protein DOI: 10.3109/1040841X.2013.870968 (Sanchez-Piris et al, 2002.…”
Section: Cell Cycle Progression In Oxidative Stress: the Role Of Sty1mentioning
confidence: 99%
See 1 more Smart Citation
“…Hog1 is the sole stress-activated MAPK in budding yeast, and Sty1 is the sole stress-activated MAPK in fission yeast. In budding yeast, two paralogous genes encode the MAPKAPKs Rck1 and Rck2 (8), and in fission yeast the corresponding proteins are Mkp1/Srk1 and Mkp2/Cmk2 (1,3,36). Similar to the situation in mammalian cells, Hog1 forms a relatively stable complex with Rck2 in budding yeast (5) and Sty1 with Mkp1/Srk1 in fission yeast (3,36), and in both organisms, the MAPK phosphorylates the cognate downstream kinase when activated by stress (3-5, 36, 39).…”
mentioning
confidence: 99%
“…In addition, Sty1/Spc1 binds and phosphorylates two downstream kinases, Cmk2 and Srk1 (Sty1-regulated kinase), which are related to the mammalian calmodulin-dependent kinases, MAPKAP kinases and to the budding yeast RCK1 and RCK2 kinases, which were identified as suppressors of a checkpoint mutant (Dahlkvist et al, 1995;Alemany et al, 2002;Smith et al, 2002).…”
Section: Introductionmentioning
confidence: 99%